Correlates of blood pressure and blood glucose screenings in Cameroon: insights from the 2018 Demographic and Health Survey. Issue 2 (12th June 2021) - Duodu, Precious Adade; Agbadi, Pascal; Duah, Henry Ofori; Darkwah, Ernest; Nutor, Jerry John
Abstract: Background: Hypertension and diabetes, two major risk factors for cardiometabolic diseases, are associated with high morbidity and mortality rates. Early detection through screening can initiate early treatment to reduce adverse outcomes. The current study sought to investigate the correlates of blood pressure and blood glucose screenings in Cameroon. Methods: We used secondary data from the 2018 Cameroon Demographic and Health Survey. Adjusting for a complex sample design, we performed multivariate prevalence ratio estimates of the blood pressure and blood glucose screenings. Results: Approximately 60% and 30% of Cameroonians had undergone blood pressure and blood glucose screenings, respectively. More females (68%) had undergone blood pressure screenings compared with their male counterparts (44.1%). In the multivariate model, gender, age, education, marital status, household wealth index and region of residence were significantly associated with both blood pressure and blood glucose screenings in the full sample. Previous blood pressure screening was associated with an increased likelihood of blood glucose screening and vice versa. A modification effect of gender was observed in the association between the correlates and both outcomes. Conclusion: Our findings uncovered individuals with a decreased likelihood for blood pressure and blood glucose screenings and this can inform policy decisions to ensure targeted screening aimed at early detection and management.